FINANCIAL ACCOUNTABILITY PRACTICE OF FAITH-BASED ORGANIZATIONS – CASE STUDY THIRD SECTOR ORGANIZATIONS IN THE SPECIAL REGION OF YOGYAKARTA - Anto Listianto, Gabriel; Antonius Diksa Kuntara (Universitas Tidar, 2022)
This study aims to describe the practice of financial accountability in two third-sector organizations, both of them are organization under religious institutions or recently named as Faith-Based Organizations (FBO). The data was gathered using interview and documentation and was analyzed using qualitative interpretive approach. The results show that in general, the two organizations apply different patterns of financial accountability, starting from planning activities in the form of participatory and tiered budgets, implementing activities, and reporting activities that vary according to the type of organization. Financial accountability practices that occur reflect the uniqueness of stakeholders, types of donors, and the scale of each FBO. Keywords: Financial accountability, third sector organization, faith-based organization